Thoracic myelopathy of discogenic origin: case report (Research, Society and Development, 2022)
Disc herniation results from degenerative disc disease. This pathological condition of the intervertebral disc is an integral part of the degenerative disease of the spine, in which several elements of the vertebral functional unit in different segments and levels are affected. Among these elements, it is possible to highlight the bone structure, ligaments, joints and intervertebral discs. Thus, the present research aims to describe the case report of a patient with Thoracic Myelopathy, in addition to showing the entire clinical history, from the onset of symptoms, disease evolution, as well as the conduct after imaging diagnosis, symptomatic improvement after surgical approach and the expected result. The case is of a patient complaining of pain and numbness in the lower limbs, which started insidiously and progressively worsened for 8 (months) months, diagnosed with thoracic myelopathy and surgically treated, which allowed a good recovery and a retracted growth. Therefore, the patient evolved well in the postoperative period, with complete recovery of motor and sensory deficits.